Sputum cysteinyl leukotrienes increase 24 hours after allergen inhalation in atopic asthmatics. - Macfarlane, A; Dworski, R; Sheller, JR; Pavord, I; Kay, AB; Barnes, N (2000)
We have used the relatively noninvasive technique of induced sputum to measure allergen-induced changes in the concentration of eicosanoid mediators in bronchial secretions from atopic asthmatics. Sputum induction was performed before and 24 h after inhalational allergen challenge in 14 atopic asthmatics who developed a late asthmatic reaction (LAR). Differential cell counts were made on sputum cytospins and eicosanoid (cysteinyl leukotrienes [cys LTs], prostaglandin D(2) [PGD(2)], and PGE(2)) concentrations were measured in the sputum supernatants. The percentage of eosinophils at baseline correlated with the concentration of cys LTs (r = 0.84, p < 0.001) but not prostanoid mediators. Allergen challenge produced a significant increase in the concentration of sputum cys LTs from 3. 45 ng/ml sputum to 11.95 ng/ml (p = 0.002), which correlated with the increase in sputum eosinophils (r = 0.55, p < 0.05). There were no significant changes in PGD(2) or PGE(2) concentrations in sputum supernatants in response to challenge. Thus, the noninvasive technique of induced sputum has been used to demonstrate increased cys LTs, but not prostanoids associated with LAR after allergen challenge. The correlation between eosinophil numbers and cys LT concentrations at baseline values and 24 h after allergen challenge is consistent with these cells being a principal source of cys LTs within the airways at these time points.